Rereading the history of recreation in Canada: Moving beyond the politics of health. Issue 4 (2nd October 2019) - Tink, Lisa N.; Peers, Danielle; Nykiforuk, Candace I. J.; Mayan, Maria
ABSTRACT: In recent years there has been an increase in the number of recreation and public health professionals calling for a common agenda to address physical inactivity. A major reason for this has been the growing acceptance of recreation as a legitimate health partner. What is missed in these recent calls to bring recreation into conversation with health-related fields is that recreation policies and practices have largely emerged within the context of public health interventions. In order to address this gap in the literature, this paper uses Foucault's analysis of social medicine to highlight how recreation already is, and has long been, a governmental practice built around the social and political objectives of public health. Recognizing the need to reorient how recreation is positioned in contemporary society, it ends by suggesting some alternative directions for recreation and introducing some philosophical questions about the future of recreation services in Canada.